Crenças sobre a cura da homossexualidade: uma explicação a partir de variáveis socioculturais - Rezende, Alessandro Teixeira (2021)
This thesis aimed to verify the extent to which socio-cultural variables (i.e., attitudes towards gays and lesbians, sexual prejudice, orientation towards social dominance and human values) explain beliefs about the cure for homosexuality. To this end, six articles were prepared. In Article 1, a systematic review was carried out on the study of the cure for homosexuality in the last 19 years, seeking to understand how this theme has been studied in different areas of knowledge (e.g., law, psychology, psychiatry). The present review demonstrated that for almost a decade professionals in psychology and psychiatry have used scientific knowledge to legitimize practices aimed at the supposed cure of homosexuality. Article 2, of an empirical and qualitative nature, sought to map through the social discourses the beliefs associated with the cure of homosexuality. 237 university students participated (Midade = 21.0; SD = 5.07), who answered, in addition to sociodemographic questions, an interview script composed of three open questions. In summary, despite the exploratory nature and the absence of empirical evidence in the Brazilian context regarding the beliefs about “gay cure”, the results pointed to the existence of six classes aimed at the unfavorability in relation to the professionals who support treatments of reversal of orientation sexual. Article 3, on the other hand, dealt with the elaboration of the Scale of Beliefs on Healing Homosexuality (ECCH), whose items were constructed based on the literature in the area. 225 university students participated in this study (Midade = 21.0; SD = 5.78), who answered the initial version of the ECCH, composed of 36 items, and demographic questions. A principal component analysis indicated a pentafactorial solution for the measurement, with acceptable reliability indicators. The dimensions were named as religious beliefs (α = 0.95), moral beliefs (α = 0.95), biological beliefs (α = 0.96), psychological beliefs (α = 0.92), these dimensions being favorable to cure of homosexuality, and, finally, a dimension of beliefs unfavorable to sexual reversion (α = 0.93). Each of the dimensions brought together four items in the final version of the instrument. These dimensions were correlated to measures of beliefs about homosexuality (ECH) and social desirability (EDSMC), with correlations being observed in the expected directions. Because the analyzes presented so far are eminently exploratory, it was decided to elaborate Article 4, which aimed to confirm the previously observed factorial structure (N = 215), and whose results indicated a satisfactory fit for the pentafactorial model (eg, CFI = 0.95; TLI = 0.94; RMSEA = 0.06). Subsequently, seeking to gather evidence of convergent validity, new participants (N = 430 university students; Midade = 23.5; SD = 7.90) responded to measures of sexual prejudice (EMPS) and attitudes towards gays and lesbians (EMAFGL). The results indicated that the dimensions of the ECCH showed strong correlations in the expected direction. With preliminary evidence attesting the adequacy of ECCH, we started with Article 5, aiming to know the predictive power of the dimensions of sexual prejudice and attitudes towards gays and lesbians in relation to the dis (favorability) to cure homosexuality, proposing and testing two explanatory models. To this end, 375 university students participated (Midade = 21.7; SD = 6.80), who answered EMPS, EMAFGL and ECCH, in addition to sociodemographic questions. The results indicated the theoretical and empirical adequacy of the models of favorability (eg, CFI = 0.98; TLI = 0.97; RMSEA = 0.07) and unfavorability to the cure of homosexuality (eg, CFI = 0.99; TLI = 1.00; RMSEA = 0.03). Finally, seeking to gather additional evidence regarding beliefs about the cure for homosexuality, Article 6 was carried out, in which it sought to verify the predictive power of the SDO and human values in relation to these beliefs. 391 people from the general population participated (Midade = 25.7; SD = 7.20), who answered the ECCH, the Social Dominance Orientation Scale (SDO), the Basic Values Questionnaire (QVB) and sociodemographic questions. The results indicated that the SDG and human values were good predictors of beliefs about curing homosexuality (p <0.001). Furthermore, the proposed mediation models, which considered beliefs separately as dependent variables, SDO as an independent variable and normative values as a mediating variable, obtained significant indirect effects, demonstrating that the SDO explains all beliefs through normative values (p < 0.001). It is estimated that the objectives proposed in this thesis have been achieved, and it is possible to count on a measure to evaluate the beliefs about the cure of psychometrically adequate homosexuality, with evidence of validity (eg, factorial, convergent and discriminating) and satisfactory internal consistency, in addition to to broaden the understanding around these beliefs based on their relationships with other psychosocial constructs.